Ten years of recreational diving fatalities in the United States and Canada: harvesters vs non-harvesters - Rowley, B.; Buzzacott, Peter; Denoble, P. (Wiley-Blackwell Publishing, Inc., 2016)
© International Society of Travel Medicine, 2016. Published by Oxford University Press. All rights reserved. For Permissions, please e-mail: journals.permissions@oup.com. Adult male recreational diver fatalities (n = 698) in North America from 2004 to 2013 were examined. Compared with non-harvesters, boat (86 vs 59%), solo (26 vs 13%) and night diving (10 vs 3%) were more common among harvesters. Of the divers who were low-on or out-of air, 20% were harvesters and 11% non-harvesters (OR?=?2.0, P = 0.03).